Strategi Pendampingan Dalam Meningkatkan Keterampilan Membaca Al-Qur’an Di TPA Al-Mubarokah Sukaraja Baru Indralaya Selatan Ogan Ilir - Wahidin Wahidin; Agustin Rozalena; Icuk M. Sakir (Janaka, Jurnal Pengabdian Masyarakat, 2022)
This community service was carried out in Sukaraja Baru Village, South Indralaya Ogan Ilir. After conducting a survey of the children's recitation sites, data were obtained on TPA Nurul Amal, TPA Ar-Rahman and TPA Al-Mubarokah. Community service activities at TPA Al-Mubarokah because the children at this place of recitation are not fluent in reading and writing calligraphy. The aim is to hold socialization activities regarding mentoring strategies in improving Al-Qur'an reading for children, holding calligraphy competitions for children and inviting the community to participate in recitation activity programs. Methods of data collection by home visits, observations and interviews. From the results of these activities the children were able to make calligraphy works and were able to read the Qur'an fluently. The conclusions are (1) The process of mentoring learning to read the Koran and write calligraphy has been successful. (2) Children are more active in reciting and writing calligraphy by participating in competitions at the village level. (3) This community service activity can strengthen cooperation between STISIPOL Candradimuka and Sukaraja Baru Village officials and TPA Al-Mubarokah. (4) This activity will bring great benefits to the children and after this activity the closeness between communities is maintained.